Epithelial salivary gland tumors in pediatric patients: An international collaborative study. (May 2023) - Quixabeira Oliveira, Gabriella Alves; Pérez-DE-Oliveira, Maria Eduarda; Robinson, Liam; Khurram, Syed Ali; Hunter, Keith; Speight, Paul M.; Kowalski, Luiz Paulo; Lopes Pinto, Clóvis Antonio; Sales De Sá, Raísa; Mendonça, Elismauro Francisco; Sousa-Neto, Sebastião Silvério; de Carlucci Junior, Dorival; et al.
Abstract: Objective: Salivary gland tumors (SGT) are a diverse group of uncommon neoplasms that are rare in pediatric patients. This study aimed to characterize the clinicopathological profile of pediatric patients affected by SGT from a large case series derived from an international group of academic centers. Study design: A retrospective analysis of pediatric patients with SGT (0–19 years old) diagnosed between 2000 and 2021 from Brazil, South Africa, and the United Kingdom was performed. SPSS Statistics for Windows was used for a quantitative analysis of the data, with a descriptive analysis of the clinicopathological characteristics and the association between clinical variables and diagnoses. Results: A total of 203 cases of epithelial SGT were included. Females were slightly more commonly (56.5%), with a mean age of 14.1 years. The palate was the most common site (43.5%), followed by the parotid gland (29%), lip (10%), and submandibular gland (7.5%). The predominant clinical presentation was a flesh-colored, smooth, and painless nodule. Pleomorphic adenoma (PA) was the most frequently diagnosed SGT (58.6%), followed by mucoepidermoid carcinoma (MEC) (26.6%). Surgery (90.8%) was the favored treatment option. Conclusions: Benign SGT in pediatric patients are more commonly benign than malignant tumors. Clinicians should keep PA and MEC in mind when assessing nodular lesions of possible salivary gland origin in pediatric patients.